2016
DOI: 10.1177/1557085115620479
|View full text |Cite
|
Sign up to set email alerts
|

Gender Equality, Place, and Female-Victim Intimate Partner Homicide

Abstract: Assessments of the relationship between gender equality and gendered homicide have led to the development of two primary literatures: the first exploring backlash and amelioration effects, and the second examining the influence of exposure reduction. In addition, a third body of research has examined differences in intimate partner homicide (IPH) between rural and non-rural places. The current study contributes to these three literatures by exploring the relationship between gender equality and female-victim I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 31 publications
1
56
0
Order By: Relevance
“…Whereas in urban areas, relative gender statuses have seemed to be more influential on male victim IPH, there is some evidence that these factors may be important in rural areas. Gillespie and Reckdenwald (2017) found that in rural North Carolina, an increase in relative female employment and education was associated with a decrease in female victim IPH when controlling for poverty (Gillespie & Reckdenwald, 2017). Overall, while the literature reports mixed findings about gender equality's relationship to IPH in urban centers, in rural communities, county-level gender equality may be protective against female victim IPH (Gillespie & Reckdenwald, 2017).…”
Section: Gender Equality Characteristicsmentioning
confidence: 99%
“…Whereas in urban areas, relative gender statuses have seemed to be more influential on male victim IPH, there is some evidence that these factors may be important in rural areas. Gillespie and Reckdenwald (2017) found that in rural North Carolina, an increase in relative female employment and education was associated with a decrease in female victim IPH when controlling for poverty (Gillespie & Reckdenwald, 2017). Overall, while the literature reports mixed findings about gender equality's relationship to IPH in urban centers, in rural communities, county-level gender equality may be protective against female victim IPH (Gillespie & Reckdenwald, 2017).…”
Section: Gender Equality Characteristicsmentioning
confidence: 99%
“…Dawson et al, 2009;Dugan et al, 2003;Dugan et al, 1999;Reckdenwald & Parker, 2012). It has further been highlighted that research addressing the link between availability of domestic violence resources and IPH rates is lacking (Dawson et al, 2009;Gillespie & Reckdenwald, 2017). Up to date, it has been disclosed that the link between domestic violence resources and IPH rates is complex (Dawson et al, 2009;Dugan et al, 2003).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…In terms of geographic setting, it has been underlined that the potential influence of rurality needs to be considered in analyses of IPH and IPH rates (Gillespie & Reckdenwald, 2017;Jennings & Piquero, 2008). Shannon, Logan, Cole, and Medley (2006) has highlighted that the domestic violence resources are predominantly provided in urban areas, while less available in the rural areas.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Conversely, in urban areas, the rate of federal firearm licensees (FFLs) may increase ease of access to obtain a firearm having a greater impact on those that do not already own a gun (Semenza et al, 2020;. The higher rate of pre-existing gun ownership in rural areas can be partially attributed to the unique "gun culture" that exists in rural areas (Cunningham et al, 2000;Gillespie & Reckdenwald, 2017;Steidley et al, 2017;Websdale, 1998;Wiebe et al, 2009). This gun culture signifies increased cultural acceptance for owning guns, due to traditional uses in hunting and sport, heritage and sentimental values associated with guns and guns passed down from generation to generation, and the idea of growing up around guns (Azrael et al, 2004;Williams, 2003).…”
Section: Firearm Availabilitymentioning
confidence: 99%
“…In one of the first population-based studies of the prevalence of IPV among the general population, Breiding and his colleagues (2009) estimated approximately 27% of rural women have experienced some sort of lifetime IPV victimization. Though some estimates suggest partner violence rates are similar between rural and non-rural areas (Brieding et al, 2009), the seriousness of partner violence is often exacerbated in rural areas due to social isolation and reduced access to support and healthcare services for victims (Gillespie & Reckdenwald, 2017;Peek-Asa et al, 2011), as well as cultural conditions impacting the reporting and deterrability of violence between intimate partners. This can amount to unique vulnerabilities among rural women, especially those who are divorced or separated (Edwards, 2015).…”
Section: Introductionmentioning
confidence: 99%